A Qualitative And Quantitative Assessment Of Starz-Drp For Triage Action Plan, Determine Drug-Related Problem And Counsel Self-Care Customer In Malaysia Community Pharmacies - Nordin, Nazri (2018)
The roles of the community pharmacists (CPs) are currently evolving from providing product-oriented to patient-oriented services. Such course of action might have potential to enhance the image of CPs in the healthcare settings. Nonetheless, the scenario might not be possible to implement in Malaysia. For that reason, it is essential to examine the perspectives of relevant stakeholders in Malaysia regarding CPs’ extended roles. Foremost, it is critical to determine the possibility of putting in the picture of a prospective approach to help CPs to perform their extended roles particularly in making a triaging action plan and identifying drug-related problems (DRPs). The primary objective of the study is to perform qualitative research to investigate the perceptions among the relevant stakeholders of CPs’ roles and STARZ-DRP as a prospective instrument to perform the triaging activity as well as to determine DRPs. The study’s second objective is to execute a quantitative study to generate the content validity evidence for each construct item in STARZ-DRP to substantiate it a possible instrument to assist CPs executing their role as a medication protector. In the qualitative study, a group of stakeholders (n = 12) involved in a face-to-face interview. The interviewer used a semi-structured questionnaire to obtain the data about their ideas, feelings, and perceptions of the matter in question. The study was audio-taped, transcribed and coded to determine the themes. In the quantitative study, a group of lay and content experts was invited to involve in the content validity test.